Dwanaście kolumn z Gortyny — historia odkrycia - Szymańska, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is devoted to the history of the discovery of the so-called Code of Gortyn, which has attracted the interest of philologists and historians of law. The Code of Gortyn was discovered in the late 19th century by chance, yet the discovery was linked to large-scale archaeological research conducted on the island by the French, Germans and Italians. Its most extensive fragment was found by the Italian scholar Frederico Halbherr, who is consequently regarded as its discoverer, although we should not forget about the contributions of French scholars working independently, about the assistance provided by Ernst Fabricius and about the contributions of local scholars
Keywords: Kreta; Gortyna; Kodeks z Gortyny; Halbherr, Frederico (1857-1930)